Liquid sloshing in a horizontally forced vessel with bottom topography. (July 2016) - Turner, M.R.
Abstract: This paper presents a numerical study of the free-surface evolution for inviscid, incompressible, irrotational, horizontally forced sloshing in a two-dimensional rectangular vessel with an inhomogeneous bottom topography. The numerical scheme uses a time-dependent conformal mapping to map the physical fluid domain to a rectangle in the computational domain with a time-dependent aspect ratio Q ( t ), known as the conformal modulus. The advantage of this approach over conventional potential flow solvers is the solution automatically satisfies Laplace's equation for all time, hence only the integration of the two free-surface boundary conditions is required. This makes the scheme computationally fast, and as grid points are required only along the free-surface, high resolution simulations can be performed which allows for simulations for mean fluid depths close to the shallow water water regime. The scheme is robust and can simulate both resonate and non-resonate cases, where in the former, the large amplitude waves are well predicted. Results of nonlinear simulations are presented in the case of non-breaking waves for both an asymmetrical 'step' and a symmetric 'hump' bottom topography. The natural free-sloshing mode frequencies are compared with the small topography asymptotic results ofFaltinsen and Timokha (2009) ( Sloshing, Cambridge University Press (Cambridge)), and are found to be lower than this asymptotic prediction for moderate and large topography magnitudes. For forced periodic oscillations it is shown that the hump profile is the most effective topography for minimizing the nonlinear response of the fluid, and hence this topography would reduce the stresses on the vessel walls generated by the fluid. Results also show that varying the width of the step or hump has a less significant effect than varying its magnitude. Abstract : Highlights: Fluid sloshing in rectangular vessel with bottom topography is studied. Numerical method uses conformal mapping to increase computational speed. Results show that hump profiles are most effective fluid dampers.